Telling stories: exploring the relationship between myths and ecological wisdom - Eidinow, Esther (Elsevier, 2016)
This paper proposes that “myths” and myth-making can provide a framework for not only capturing ecological wisdom within its specialist domains, but also transmitting it as actionable knowledge beyond the boundaries of those domains. It argues that understanding the relationship between myth and “wisdoms” can lead to a powerful process for thinking about ecological futures, which may be realized through a strategic process such as scenario- planning.